Concerted transport and phosphorylation of diacylglycerol at ER–PM contact sites regulate phospholipid dynamics during stress - Selene Garcia-Hernandez; Jorge Morello-López; Richard Haslam; Vitor Amorim-Silva; José Moya-Cuevas; Rafael Catalá; Louise Michaelson; Jessica Pérez-Sancho; Vedrana Marković; Julio Salinas; Johnathan Napier; Yvon Jaillais; et al. (Proceedings of the National Academy of Sciences, 2025)
A universal response of plants to environmental stresses is the activation of plasma membrane (PM) phospholipase C, which hydrolyzes phosphoinositides to produce soluble inositol phosphate and diacylglycerol (DAG). Because of their conical shape, DAG amounts have to be tightly regulated or they can destabilize membranes. We previously showed that upon stress, Synaptotagmin1 (SYT1) transports DAG from the PM to the endoplasmic reticulum (ER) at ER–PM Contact Sites (CS). Here, we addressed the fate of the incoming DAG in the ER. We show that diacylglycerol kinases (DGKs) DGK1 and DGK2 form a module with SYT1 functionally coupling DAG transport and phosphorylation at ER–PM CS. Although SYT1 and DGK1/DGK2 do not show exclusive ER–PM CS localization, their interaction occurs specifically at ER–PM CS and the removal of ER–PM CS abolishes the interaction. Lipidomic analysis of a dgk1dgk2 double mutant supports that DGK1 and DGK2 phosphorylate DAG at the ER and transcriptomic and phenotypic analyses indicate that SYT1 and DGK1/DGK2 are functionally related. Taken together, our results highlight a mechanism at ER–PM CS that coordinates the transfer of DAG from the PM to the ER by SYT1 upon stress and the concomitant phosphorylation of DAG by DGK1 and DGK2 at the ER. These findings underscore the critical role of spatial coordination in lipid metabolism during stress-induced membrane remodeling.